Proverbs: a form of paremiological cliché - Mansurova , Evelina (The Lingua Spectrum, 2025)
The review article investigates proverbs as a distinct category of paremiological clichés, emphasizing their relevance in linguistic and cultural studies. It outlines various theoretical approaches that characterize proverbs as stereotyped expressions, while clearly distinguishing them from sayings. By analyzing the structural and semantic aspects of proverbs, the article draws on the works of both Russian and international linguists to provide a comprehensive understanding. The study identifies key features that differentiate proverbs from sayings, addressing their unique functions within language and culture. Furthermore, it highlights the significance of paremiological clichés as reflections of cultural code, which serve as valuable tools for categorizing life experiences. Proverbs play a crucial role in shaping broader outlook, particularly in the context of cross-cultural interactions. Ultimately, the article highlights the significance of paremiology and the necessity of studying proverbs to attain a comprehensive understanding of the cultural richness of any language.